A review of impact loads on composite wind turbine blades: Impact threats and classification. (May 2023) - Verma, Amrit Shankar; Yan, Jiquan; Hu, Weifei; Jiang, Zhiyu; Shi, Wei; Teuwen, Julie J.E.
Abstract: A fiber-reinforced composite wind turbine blade (WTB) is exposed to numerous impact threats during its service life causing damages that can be detrimental to its structural integrity. Currently, impact loads are not considered during blade design, so high safety factors are introduced, which result in a conservative design. However, as wind turbine blades become stiffer and lighter and health monitoring systems become more sophisticated, the design process is shifting toward damage-tolerant approaches. The design philosophy accepts damages to the structure, but it also requires that the damaged blade still meet structural and functional requirements. This design procedure requires a comprehensive understanding of different impact threats and their characteristics, which is currently unavailable in the public domain. This paper is a first attempt to review the impact loads on composite wind turbine blades. The aim of the current paper is to (a) identify different sources of impact threats on wind turbine blades during different stages of their service life, (b) describe their qualitative (causes and vulnerable regions) as well as quantitative characteristics (size, mass, and velocity of impactor), and to (c) provide modeling guidelines by comparing these impact threats using five different criteria - (i) relative deformability of projectile and wind turbine blade, (ii) impact velocity, (iii) kinetic energy of impact, (iv) repeatability of impacts and (v) nature of the impact. The review paper will be of special interest to researchers working on wind turbine blades and will serve as a baseline report for designing damage-tolerant blades. Recommendations are also provided for future research. Highlights: Different sources of impact threats are identified on wind turbine blades during different stages of their service life. Qualitative and quantitative characteristics of impact Loads are comprehensively described. Modeling guidelines are provided by comparing the impact threats using five different criteria.